Classification of Executive Authorities in the Field of Scientific, Scientific and Technical Activities in Ukraine - V. S. Tarasenko (Bulletin of Kharkiv National University of Internal Affairs)
As a result of the conducted scientific research the range of executive agencies in the field of scientific, scientific and technical activity in Ukraine has been established. The latter are not individually represented in the mechanism of the state apparatus. Nowadays they include: the Cabinet of Ministers of Ukraine, the Ministry of Education and Science of Ukraine, the Ministry of Strategic Industries of Ukraine, the Ministry of Energy of Ukraine, the Ministry of Economic Development, Trade and Agriculture of Ukraine, the Ministry of Internal Affairs of Ukraine, the Ministry of Protecting Environment and Natural Resources of Ukraine, the Ministry of Infrastructure of Ukraine, the Ministry of Health of Ukraine, the Ministry of Justice of Ukraine, the Council of Ministers of the Autonomous Republic of Crimea and local state administrations.